Nanoparticles from Gantrez-based conjugates for the oral delivery of camptothecin - Judit Huarte; Socorro Espuelas; Cristina Martínez-Oharriz; Juan M. Irache (Elsevier, 2021)
Camptothecin (CPT) exhibits a number of challenges for its oral administration, including a low aqueous solubility, a lactone ring susceptible to hydrolysis, and an affinity to the intestinal P-gp. The aim of this work was to evaluate nanoparticles from Gantrez-based conjugates as carriers for the oral delivery of CPT. For this purpose two different conjugates (G-mPEG and G-HPCD), obtained by the covalent binding of either HP-β-CD or methoxy-PEG (m-PEG) to the polymer backbone of Gantrez™ AN, were synthetized and characterized. Both excipients (m-PEG and HPCD) were selected due to their reported abilities to stabilize the lactone ring of CPT and disturb the effect of intestinal P-gp. The resulting nanoparticles (G-mPEG-NP and G-HPCD-NP) presented a similar size (about 200 nm) and zeta potential (close to −35 mV); although, G-mPEG-NP presented a higher CPT payload than G-HPCD-NP. On the contrary, in rats, nanoparticles based on Gantrez conjugates appeared to be capable of crossing the protective mucus layer and reach the intestinal epithelium, whereas conventional Gantrez nanoparticles displayed a mucoadhesive profile. Finally, the pharmacokinetic study revealed that both formulations were able to enhance the relative oral bioavailability of CPT; although this value was found to be 2.6-times higher for G-mPEG-NP than for G-HPCD-NP.